2011
DOI: 10.1038/onc.2011.102
|View full text |Cite
|
Sign up to set email alerts
|

TXNIP potentiates Redd1-induced mTOR suppression through stabilization of Redd1

Abstract: The mammalian target of rapamycin (mTOR) is a highly conserved serine-threonine kinase activated in response to growth factors and nutrients. Because of frequent dysregulation of the mTOR signaling pathway in diverse human cancers, this kinase is a key therapeutic target. Redd1 is a negative regulator of mTOR, mediating dissociation of 14-3-3 from tuberous sclerosis complex (TSC)2, which allows formation of a TSC-TSC2 complex. In the present study, we identify TXNIP that inhibits mTOR activity by binding to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 39 publications
4
55
1
Order By: Relevance
“…7A), suggesting that the MondoA-TXNIP axis is required for the full metabolic stress response triggered by mTORC1 suppression. TXNIP has previously been shown to reduce mTORC1 activity via stabilization of Redd1, which drives TSC1/2 complex formation (34). However, our studies in TSC2-KO MEFs suggest that TXNIP can reduce mTORC1 activity independent of Redd1 and TSC2 (Fig.…”
Section: Discussioncontrasting
confidence: 54%
“…7A), suggesting that the MondoA-TXNIP axis is required for the full metabolic stress response triggered by mTORC1 suppression. TXNIP has previously been shown to reduce mTORC1 activity via stabilization of Redd1, which drives TSC1/2 complex formation (34). However, our studies in TSC2-KO MEFs suggest that TXNIP can reduce mTORC1 activity independent of Redd1 and TSC2 (Fig.…”
Section: Discussioncontrasting
confidence: 54%
“…As a result of the broad cellular roles of thioredoxin, Txnip is implicated in diverse cellular processes including proliferation, apoptosis, and differentiation (34). A recent study identified TXNIP as an upstream regulator of mTOR activity (35), but here we report mTOR as a regulator of TXNIP. TXNIP was significantly up-regulated by PP242 but not by rapamycin or DG2 (Fig.…”
Section: Pp242 But Not Rapamycin Causes Global Transcriptional Rewiringmentioning
confidence: 70%
“…Regulated in development and DNA damage responses 1 (Redd1) protein is a negative regulator of mTOR activity. Txnip interacts with Redd1 and protects it from proteasomal degradation, leading to decreased mTOR activity (130).…”
mentioning
confidence: 99%